Upaya Peningkatan Nilai CBR Tanah Lempung Menggunakan Campuran Kapur, Abu Sekam, dan Serat Fiber - Indrayani Indrayani; Andi Herius; Puryanto Puryanto; Revias Noerdin; Maharu Ismail; Siti Aisyah (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2022)
Soil is an important element in supporting development activities in the world of civil construction. One type of soil that is often found in South Sumatra is clay. Clay soil is a type of fine-grained soil that is strongly influenced by water content. Each type of clay has a different carrying capacity value. Therefore, an analysis is needed to test the effect of adding a mixture of materials to the clay. A test was carried out to see the effect of adding mixed materials to the soil. In this test, soil samples were taken from the Banyuasin district and mixed with materials in the form of fiber, husk ash, and lime. For variations in soil mixture testing, 0.1% fiber, 2.5% husk ash, and lime consist of 2.5%, 5%, and 7.5%, as well as plain water. The test results show that the addition of a mixture of fiber, husk ash, and cement can improve the physical and mechanical properties of clay, where the optimum addition variation in the 4th variation is a mixture of soil + fiber 0.1% + husk ash 2.5% + lime 5%, which is 52.49%.